2020
DOI: 10.20469/ijbas.6.10001-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Measurement of Customer Experience Management

Abstract: This study is built upon empirical testing of an exceedingly important theme of Customer Experience Management (CEM). It prompts positive behavioural intentions of the shoppers visiting the banks with a fundamental component of customer satisfaction by using social exchange theory. Data (N = 330) was collected by utilizing a survey strategy through convenience sampling and cross-sectional research design. SPSS 20 and AMOS 22 were applied for the data analysis. To evaluate the hidden system of customer satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…4.1.1 Discriminant validity. Henseler et al (2015) suggested that Heterotrait-Monotrait (HTMT) ratio is a more accurate measure of discriminant validity while using smart PLS (Mansoor et al, 2020). The HTMT ratio value should be less than 0.9, as depicted in Table 2 that all values were less than 0.9 for the entire model (Figure 2).…”
Section: Assessing the Measurement Modelmentioning
confidence: 98%
“…4.1.1 Discriminant validity. Henseler et al (2015) suggested that Heterotrait-Monotrait (HTMT) ratio is a more accurate measure of discriminant validity while using smart PLS (Mansoor et al, 2020). The HTMT ratio value should be less than 0.9, as depicted in Table 2 that all values were less than 0.9 for the entire model (Figure 2).…”
Section: Assessing the Measurement Modelmentioning
confidence: 98%
“…Transformasi dalam sistem perbankan sebagai preferensi saat ini. Penting untuk diingat di sini bahwa pengalaman pelanggan selalu menjadi pertimbangan penting bagi organisasi (Mansoor et al, 2020).…”
Section: Pendahuluanunclassified
“…ANOVA results revealed that age and period in marriage significantly affected the dependent variable; therefore, both were controlled during further analysis. To test the current study's hypotheses, PLS-SEM (Partial Least Square-Structural Equation Model) in SmartPLS version 3.2.8 was used [31,32,33]. This study has focused more on PLS-SEM as compared to CB-SEM (Covariance Based-Structural Equation Model).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%